Case report: Zanubrutinib-induced dermatological toxicities: A single-center experience and review - Wang, Lingling; Tang, Jiao; Feng, Jun; Huang, Yongfen; Cheng, Yuexin; Xu, Hao; Miao, Yuqing (Frontiers in Oncology, 2022)
Zanubrutinib, a next-generation non-covalent Bruton’s tyrosine kinase (BTK) inhibitor, shows great efficacy in the treatment of B cell malignancies. Some patients may experience a series of side effects after the treatment of zanubrutinib. Grade 4 dermatological toxicities are rare, which present as severe rash and skin infection. Herein, we retrospectively reported the grade 4 dermatological toxicities of zanubrutinib in three consecutive patients. They were treated with zanubrutinib 160 mg twice daily orally. One patient was diagnosed with Primary Breast Diffuse Large B-cell Lymphoma(PB-DLBCL) and two patients were diagnosed with Chronic Lymphocytic Leukemia(CLL). Within one month after zanubrutinib treatment, all three patients developed grade 4 dermatological toxicities, including bruising, maculopapular rash, petechiae, ecchymosis, hemorrhagic blister, acne-Like rash, papulopustular rash, and skin infections. Zanubrutinib was discontinued in two patients due to unacceptable dermatological toxicities. Safety data from pre-licensing clinical trials showed that zanubrutinib-related side effects were frequent but well tolerated. To date, no severe dermatological toxicities were reported. The majority of patients can be relieved with symptomatic treatment, but a very small percentage of patients may face discontinuation of the drug.